Https://us-static.z-dn.net/files/d8d/e008ced388704d59896d3bf37158f465.jpeg
Answer:
Let's simplify step-by-step.
3e−6e+3e−4e
=3e+−6e+3e+−4e
Combine Like Terms:
=3e+−6e+3e+−4e
=(3e+−6e+3e+−4e)
=−4e
Step-by-step explanation:
You are welcome
Answer:
Hello,
Step-by-step explanation:
![A=(1,2)\\B=(0,-1)\\\overrightarrow{AB}=((0,-1)-(1,2)=(-1,-3)\ ||\overrightarrow{AB}||^2=1+9=10\\\overrightarrow{BC}=((3,-2)-(0,-1)=(3,-1)\ ||\overrightarrow{BC}||^2=9+1=10\\\\Triangle\ is\ isosceles.\\\\\overrightarrow{AB}.\overrightarrow{BC}=(-1,-3)*\left[\begin{array}{c}3\\-1\end{array}\right] =-3+3=0\\\\Triangle \ is\ right.\\\\](https://tex.z-dn.net/?f=A%3D%281%2C2%29%5C%5CB%3D%280%2C-1%29%5C%5C%5Coverrightarrow%7BAB%7D%3D%28%280%2C-1%29-%281%2C2%29%3D%28-1%2C-3%29%5C%20%7C%7C%5Coverrightarrow%7BAB%7D%7C%7C%5E2%3D1%2B9%3D10%5C%5C%5Coverrightarrow%7BBC%7D%3D%28%283%2C-2%29-%280%2C-1%29%3D%283%2C-1%29%5C%20%7C%7C%5Coverrightarrow%7BBC%7D%7C%7C%5E2%3D9%2B1%3D10%5C%5C%5C%5CTriangle%5C%20is%5C%20isosceles.%5C%5C%5C%5C%5Coverrightarrow%7BAB%7D.%5Coverrightarrow%7BBC%7D%3D%28-1%2C-3%29%2A%5Cleft%5B%5Cbegin%7Barray%7D%7Bc%7D3%5C%5C-1%5Cend%7Barray%7D%5Cright%5D%20%3D-3%2B3%3D0%5C%5C%5C%5CTriangle%20%5C%20is%5C%20right.%5C%5C%5C%5C)
Answer:
c. w = -1
Step-by-step explanation:
you have to add 2 with -3 and you get -1.
Answer:
wait do you still need the answer?